Financing adaptation to climate change through budget support - Britta Horstmann; Stefan Leiderer; Imme Scholz (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Adaptation to climate change is an inevitable challenge, especially in developing countries. Recent calculations show that costs of adaptation and corresponding needs for financial support are high. The international community therefore has to face urgent questions on how to meet these financial needs on the one hand and how to channel available funds to respective developing countries and vulnerable communities on the other. In bi- and multilateral development cooperation, there is a strong trend towards programme-based approaches and general budget support for financing multi-sectoral poverty eduction strategies. These instruments can also be relevant for funding adaptation measures as a means of supporting a country-driven integration of adaptation into national policies. In order to use general budget support or programme-based approaches for adaptation funding, however, the following issues need to be addressed: (i) ensure a country-driven integration of adaptation policies into poverty reduction strategies and development planning, (ii) take a participatory approach to the policy dialogue and (iii) develop an assessment framework for monitoring and evaluation. The stablishment of an independent expert panel could support the implementation of these tasks.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Klimawandel